Clinical presentation and survival of retinoblastoma in Indian children. Issue 2 (10th June 2015) - Chawla, Bhavna; Hasan, Fahmi; Azad, Rajvardhan; Seth, Rachna; Upadhyay, Ashish Datt; Pathy, Sushmita; Pandey, RM
Abstract : Objective: To study the clinical presentation and survival among Indian children with retinoblastoma (RB) and to determine factors predictive of poor outcome. Methods: A retrospective review of children newly diagnosed with RB at a tertiary referral centre was undertaken. Demographic and clinical characteristics and treatment outcomes were studied. Results: A total of 600 patients (unilateral 67.6%, bilateral 32.4%) was studied. 61% was boys. The median age at presentation was 29 months (18 months vs 36 months in bilateral and unilateral cases, respectively, p<0.001). leukocoria was most common (83%), followed by proptosis (17%). Tumours were intraocular in 72.3% and extraocular in 27.7% cases. In the intraocular group, 78% were advanced Group D or E disease. Metastasis to the central nervous system was noted in 15.7% of extraocular cases. A statistically significant difference was seen between intraocular and extraocular groups in the median age (24 months vs 37.5 months, p<0.001) and median lag period (2.5 months vs 7 months, p<0.001). The Kaplan-Meier survival probability was 83%, 73% and 65% at 1 year, 2 years and 5 years, respectively. On univariate analysis, age >2 years (p=0.002), lag period >6 months (p=0.004) and extraocular stage (p<0.001) were associated with poor outcome. On multivariate analysis, extraocular invasion was predictive of low survival (HR 5.04, p<0.001). Conclusions: Delayed presentation is a matter of concern. Improving awareness about the early signs and creating facilities for diagnosing and treating RB at the primary and secondary levels of healthcare are required to reduce mortality and morbidity, and lead to improved outcomes that are comparable with the developed nations.